Isolation and Characterization of Bacteria Species Related to Food Contact Surfaces in Selected Cafeterias in a Tertiary Institution Campus in ABU, Zaria, Nigeria - N. Mahammed; R. T. Abagai; Y. Mohammed (Journal of Applied Sciences and Environmental Management, 2022)
The study was carried out to isolate and characterize bacterial species from selected cafeterias in tertiary institution campus in Ahmadu Bello University Zaria, Nigeria. A total of ten samples were selected for analysis which include; spoons, plates, forks, chopping boards, worktops, tables, hands, washing water, plate rinsing water1 and plate rinsing water2. The bacteriological analysis was carried out using the nutrient agar (NA) media, which was prepared by dissolving 28g of the NA powder in 1litre of distilled water, autoclaved and allowed to cool. The growth of the microorganisms were then observed and counted per ml. The identified species include; Staphylococcus aureus, Staphylococcus epidermis, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis and Bacillus anthracis. The food contact surfaces analyzed revealed that Chopping board has the highest bacterial load with 28 x 105, followed by Hand 27 x 105, Worktop 20 x 105, Table 18.8 x 105, Washing water 16 x 105, Plate 13.6 x 105, Fork 12 x 105, Spoon 7.2 x 105, plate rinsing water1 6 x 105, plate rinsing water2 5 x 105. The frequency of occurrence of the isolated organisms include; Staphylococcus aureus 3(10.3), Staphylococcus epidermis 9 (31.1), Escherichia coli 4(13.8), Klebsiella pneumonia 6(20.7), Pseudomonas aeruginosa 3(10.3), Proteus mirabilis 2(6.9) and Bacillus anthracis 2(6.9). It was observed that Staphylococcus epidermis have the highest incidence of occurrence, Bacillus anthracis and Proteus mirabilis have the least incidence of occurrence.